Mineral and bone disorders in peritoneal dialysis - imane Houem; Mina Agrou; Imane Saidi; Naima Ouzeddoun; Rabia Bayahia; Loubna Benamar (RDPLF, 2022)
Introduction Disorders of mineral and bone metabolism are common in dialysis patients and are responsible for an increased risk of fracture, cardiovascular risk and mortality. The mineral and bone disorder most frequently found in peritoneal dialysis (PD) is adynamic osteopathy. The aim of our work is to describe the mineral and bone profile of patients on peritoneal dialysis, to determine the prevalence of hyperparathyroidism in this population and to identify the risk factors associated with it. Material and method This is a cross-sectional study including all our PD patients in whom we analyzed the various clinical, biological, radiological and therapeutic data related to mineral and bone metabolism. We defined hyperparathyroidism by a parathyroid hormone (PTH) ≥ 600pg/ml and we determined the risk factors by comparing two groups : with and without hyperparathyroidism. Results We retained 85 patients whose mean age was 49.18 ± 17.28 years and the sex ratio of 0.77. The seniority in dialysis was 33.31 ± 26.68 months. Median PTH was 668 pg/ml [34-3800] with serum calcium at 87.75±7.52 mg/l, phosphatemia at 54.07±16.69 mg/l and vitamin D at 23.74±11.56 ng/ml. Hyperparathyroidism was found in 60% of patients. The risk factors for hyperparathyroidism noted in our study are: seniority in PD, high PTH before the start of dialysis, and hyperphosphatemia. The short medical follow-up before dialysis seems to play an important role in the development of secondary hyperparathyroidism. Conclusion Hyperparathyroidism is the most frequent mineral and bone disorder in our series. Factors correlated with hyperparathyroidism are length of time on dialysis, hyperphosphatemia and high parathormone levels before the start of dialysis.